2022
DOI: 10.3390/v14020422
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Host PIM Protein Kinases Reduces Mayaro Virus Replication

Abstract: Mayaro virus (MAYV) manipulates cell machinery to successfully replicate. Thus, identifying host proteins implicated in MAYV replication represents an opportunity to discover potential antiviral targets. PIM kinases are enzymes that regulate essential cell functions and also appear to be critical factors in the replication of certain viruses. In this study we explored the consequences of PIM kinase inhibition in the replication of MAYV and other arboviruses. Cytopathic effects or viral titers in samples from M… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…A handful of recent studies support the idea that Pim1 can shape innate immune responses to viruses 43,44,[56][57][58][59][60] , although the mechanisms and outcomes vary widely. Specifically, two studies showed that Pim1 inhibits virus propagation by increasing the population of neutrophils that diminish CD8 + T-cell-mediated suppression of viruses 59 or by increasing host cell death 56 .…”
Section: Discussionmentioning
confidence: 99%
“…A handful of recent studies support the idea that Pim1 can shape innate immune responses to viruses 43,44,[56][57][58][59][60] , although the mechanisms and outcomes vary widely. Specifically, two studies showed that Pim1 inhibits virus propagation by increasing the population of neutrophils that diminish CD8 + T-cell-mediated suppression of viruses 59 or by increasing host cell death 56 .…”
Section: Discussionmentioning
confidence: 99%